Vocational Education in the Irbid Governorate of Education: The Competency of School - Jarrah, Hani Yousef; Yaghmour, Kholoud Subhi (Opción, 2019)
The study aimed to identify the competencies expected to be acquired by the graduates of the higher level of basic education during studying the vocational education subject from the perspective of male and female teachers at the directorates of education in Irbid Governorate via the analytical, descriptive method using a questionnaire consisting of (24) items. As a result, the arithmetic means of the field the competencies of the functional dimension as a whole was (3.66) by a moderate degree. In conclusion, the highest score was in acquiring the skills of dealing with various personal tests qualifying for the job (4.25).